2014
DOI: 10.1039/c3nj01395b
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on interhalogen interactions in a series of isostructural organic systems

Abstract: The order of thermal expansion of the interhalogen interactions is I⋯I < Br⋯Br < Cl⋯Cl, indicating that the order of interhalogen interaction strength is I⋯I > Br⋯Br > Cl⋯Cl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 51 publications
0
44
0
Order By: Relevance
“…This situation allows a direct comparison of energies in different X•••X pairs by means of theoretical methods. However, while Cl/Br or Br/I isostructural pairs are common, the 'triple' series are very rare [12,13] especially in coordination chemistry [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This situation allows a direct comparison of energies in different X•••X pairs by means of theoretical methods. However, while Cl/Br or Br/I isostructural pairs are common, the 'triple' series are very rare [12,13] especially in coordination chemistry [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic nature of type II halogen bonding (Metrangolo & Resnati, 2014;Mukherjee & Desiraju, 2014) means that crystal structures containing these interactions are more responsive to temperature changes (thermosalient effects). Saraswatula & Saha (2014) reported that thermal expansion of inter-halogen distances is higher for lower halogens (chlorine) and a decrease in expansion was observed with an increase in the halogen-bond strength. So the behaviour of heavier halogen atom-containing species is different from that of the lower halogens.…”
Section: Compoundmentioning
confidence: 99%
“…Previously we had shown that thermal expansions of solvates are ∼25% more than that of guest-free forms in a series of interhalogen interaction mediated organic lattices. 63 Relatively small thermal expansion in the channel structures, especially in the case of BrPOT•DCM−channel system, could be due to lower guest content of the channels. In spite of having solid guest molecule in the cavity, the corresponding isostructural channel structure of BrPOT• HMB−channel (α v = 198(7) MK −1 ) exhibits stronger thermal expansion than that of BrPOT•DCM−channel but smaller thermal expansion than the BrPOT• HMB−cage-II (α v = 225(7) MK −1 ) structure.…”
Section: Interaction (Table S4) C−h• • • N and C−h• • • O Interactiomentioning
confidence: 99%